2014
DOI: 10.1371/journal.pone.0105705
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptive Alendronate-Treatment Timing and Dosage for Osteogenesis Enhancement in Human Bone Marrow-Derived Stem Cells

Abstract: Recent studies indicated that alendronate enhanced osteogenesis in osteoblasts and human bone marrow-derived stem cells. However, the time- and dose-dependent effects of Aln on ostegenic differentiation and cytotoxicity of hBMSCs remain undefined. In present study, we investigated the effective dose range and timing of hBMSCs. hBMSCs were treated with various Aln doses (1, 5 and 10 µM) according to the following groups: group A was treated with Aln during the first five days of bone medium, groups B, C and D w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…The decreased cell viability was mainly caused by apoptosis involving the caspase-3 pathway. Alendronate-induced cytotoxicity has been reported in several studies involving oral keratinocytes [18], gingival fibroblasts [21], human periodontal ligament fibroblasts [18], endothelial cells [22], and human bone-marrow-derived stem cells [23]. Those studies all found that the highest concentrations of alendronate, ranging from 10 −11 M to 100 M, had various levels of cytotoxicity to the studied cells.…”
Section: Discussionmentioning
confidence: 82%
“…The decreased cell viability was mainly caused by apoptosis involving the caspase-3 pathway. Alendronate-induced cytotoxicity has been reported in several studies involving oral keratinocytes [18], gingival fibroblasts [21], human periodontal ligament fibroblasts [18], endothelial cells [22], and human bone-marrow-derived stem cells [23]. Those studies all found that the highest concentrations of alendronate, ranging from 10 −11 M to 100 M, had various levels of cytotoxicity to the studied cells.…”
Section: Discussionmentioning
confidence: 82%
“…By this mechanism it reduces osteoclastic stress fiber and focal adhesion density, leading to a disruption of the actin cytoskeleton [38, 39]. However, low doses of alendronate have also been shown to stimulate osteoblast function in vitro [20, 40] and to modulate BMPC phenotypic induction by increasing osteogenesis and decreasing adipogenesis [4144]. Our present results are in agreement with these previous studies: in vitro exposure of BMPC to alendronate alone (at doses that have been reported in the serum and resorption lacunae of patients treated with this N-BP) [4547] increased their osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reaction was carried out with specific primers for each gene and a thermostable DNA polymerase (Gibco BRL, Bethesda, MD, USA). According to our previous report, the osteogenic marker gene changes in mRNA expression levels of BMP2 , osteocalcin , type I collagen and Cbfa1/Runx2 were then analyzed [ 21 , 22 ]. The following mouse primer pairs were used: Osteocalcin (OC) (5′-CTTGGTGCACACCTAGCAGA-3′ forward and 5′-CTCCCTCATCGTGTT GTC CCT-3′ reverse) and Cbfa1/Runx2 (5′-CGCTCCGCCCACAAATCTC-3′ forward and 5′-CCGCACGACAACCGCACCAT-3′ reverse), BMP2 (5′-TGCGGTCTCCTAAAGGTCG-3′ forward and 5′-GAGGACCTGGGGAAGCA-3′ reverse), Collagen I (5′-GGGGCAAGACAGTCATCGAA-3′ forward and 5′-GGGTGGAGGGAGTTTACACG-3′ reverse) and GAPDH (5′-ATACGGCTACAGCAACAGGG-3′ forward and 5′-GCCTCTCTTGCTCAGTGTCC-3′ reverse) as a house-keeping gene.…”
Section: Methodsmentioning
confidence: 99%